Familiarization Effects for Bilingual Letter Detection Involving Translation or Exact Text Repetition. - Thomas, Holly Krech; Healy, Alice F.; Greenberg, Seth N. (Canadian Journal of Experimental Psychology, 2007)
In two experiments, English-Spanish bilinguals read passages, performing letter detection on some passages by circling target letters as they read. Detection passages were sometimes familiarized (primed) by prior reading of the same passage or a translation of it. Participants detected letters in English passages in Experiment 1 and in Spanish passages in Experiment 2. For both experiments, a missing letter effect occurred (depressed detection accuracy on frequent function words relative to less frequent content words). Familiarization promoted overall improvements in letter detection only for English passages, suggesting that reprocessing benefits depend on high language fluency. For Spanish passages, cognates engendered greater error rates than noncognates; the visual similarity of Spanish and English cognates apparently enabled faster identification of Spanish cognates in a way unaffected by familiarization of the whole text passage. Priming by familiarized text was significantly higher when the passages were in the same language than when they were in different languages, suggesting that the reprocessing benefits are at the word level instead of the semantic level. These results are consistent with the GO model of reading (Greenberg, Healy, Koriat, & Kreiner, 2004) but require an expanded consideration of attention redistribution processes in that model. Reprinted by permission of the publisher.